Blood Creek, Pottawatomie County - Morgan, M.J.; Gent, Frank; Schnee, Angela (Kansas State University, The Chapman Center for Rural Studies, 2012)
The authors use the oral tale of the village of Blood Creek as a starting point foe their research. Using field work, genealogical inquiry, and historic documents the authors are able to piece together the history of the Blood Creek settlement in Territorial Kansas.
Dr. M.J. Morgan, Frank Gent, and Angela Schnee, “Blood Creek, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/90.
Keywords: Blood Creek; Charles L. Blood; fort-to-fort road; Juniata; Massachusetts Emigrant Aid Company; Pottawatomie County